Information technologies in the research of biodiversity : proceedings of the International Conference Information Technologies in the Research of Biodiversity, 11-14 September, 2018, Irkutsk, Russia /: proceedings of the International Conference Information Technologies in the Research of Biodiversity, 11-14 September, 2018, Irkutsk, Russia. ([2019]) - Unknown
No abstract available